Food dependent changes of the life history traits of Catopsilia pyranthe (Lepidoptera: Pieridae). Issue 4 (1st October 2020) - Mukherjee, Swarnali; Basu, Parthiba; Saha, Goutam K.; Aditya, Gautam
ABSTRACT: The effect of larval feeding on the life history traits of the mottled emigrant butterfly Catopsilia pyranthe (Linnaeus, 1758) (Lepidoptera: Pieridae) was assessed to link life history variations as a function of food availability. The 0-day-old larvae of C. pyranthe were reared with varying quantity of food (100, 200, 400, 800, 1600 and 3200 mg/day) against a control set with ad libitum food availability. Significant differences in instar duration and body weight of the larva and therefore fitness were found in relation to the amount of food available. In urban regions like Kolkata, India, disparity in food availability may induce variations in life history traits and thus fitness and survival in C. pyranthe .